Intercultural concepts in Place Cliché by Jacques Godbout - Dwyarie, Rachel Diercie; Tjahjani, Joesana (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article discusses the intercultural concepts conveyed in the essay Place Cliché by Jacques Godbout. The elaboration centers on how the narrator-actor “I” position himself in facing two cultures. This paper shows how the concepts related to interculturalism are elucidated within the text, especially through the narratoractor “I”. The identity of the narrator that intertwines with two cultures, French and American, is discovered by exposing the symbols that represent the two cultures. The French and American culture that become a part of the intercultural condition is represented in the stereotypes found in the narrator’s focalization and the textual structure. Intercultural concepts such as hybrid identity and in-between identity will be found in the construction of the narrator’s identity. The presence of those cultural factors becomes the foundation that constructs the hybrid identity of narrator-actor “I” which is the Quebec identity (Québécois). The aforementioned findings are acquired through cultural studies theories of Homi K. Bhabha and Stuart Hall. The method that is utilized is a qualitative method with critical discourse analysis theories by Teun van Dijk and semiotics by Roland Barthes.